Effect of feed type on biology and nutritional indices of black soldier fly, Hermetia illucens L. (Diptera: Stratiomyidae) - Irsyad, Andika Muhammad; Dono, Danar; Puspasari, Lindung Tri (CROPSAVER, 2023)
Hermetia illucens L. (Black Soldier Fly) larvae are used as a source of high protein for animal feed, in cultivation they must produce larvae with fast growth and development in large numbers as well as imago with a high reproductive rate. The success factor from the type of feed given, because it can affect the growth and development of the larvae. The research to find a better type of feed for the growth and development of larvae. The research conducted from March 2022 to February 2023 at the Pesticide and Environmental Toxicology Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Padjadjaran. The experiment used a completely randomized design with 4 treatments and 5 replications. The treatment used grain bran feed, rice bran with kale, bran with banana stems, and bran with chicken manure compost. The results showed that the type of grain bran feed with chicken manure compost produced better scores on net reproduction rate (2210.85 females/mother/generation), intrinsic rate of increase (46.43%), population doubling (3.6 days), proportion of live individuals (0.84 individuals), number of eggs (528.8 eggs), average weight (6.534 g), consumption rate (0.0112 g/day), relative consumption rate (0.0104 g/day), growth rate (…0,0123 g/day..), relative growth rate (0,0115 g/g/day), digestibility (3.1940%), efficiency conversion of food consumed (2.0033%), and efficiency consumption of digested food (2,2029%)  with increase respectively 4.58 times, 9.63 times, 4.61 times, 2.1 times, 2.27 times, 3.11 times, 2 times, 2.03 times, 1.14 times, 1.16 times, 2.88 times, 1.98 times, and 3.10 times compared to rice bran feed.